Kualitas Komunikasi Keluarga terhadap Pencegahan Perilaku Seksual Berisiko pada Remaja - Dina Sulistia; Annisa Febriana; Taufik Hidayat (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2024)
Risky sexual behavior is a big problem for adolescents and a challenge for parents in taking care of their adolescents. Efforts can be made to prevent the problem of risky sexual behavior by improving the quality of family communication at home. Communication is important so that adolescents are more open and close to their parents, so they can avoid negative behavior The purpose of this study was to determine the relationship between the quality of family communication and the prevention of risky sexual behavior in adolescents. The type of research is descriptive-analytic with cross-sectional design. The population in this study was 124 people with a total research sample of 61 people taken using random sampling technique. The test was conducted with SPSS using the Pearson correlation test. The results show that there is a relationship between the quality of family communication and the prevention of adolescent risky sexual behavior, P-Value 0.04. Further research needs to be done by paying attention to nursing interventions that can support the improvement of family communication towards adolescents so that efforts to prevent risky sexual behavior in adolescents increase.